Determinan Nilai Perusahaan Dengan Transparansi Informasi Sebagai Pemoderasi - Nilda Tartilla; Darmansyah Darmansyah; Choirul Anwar (Liquidity: Jurnal Riset Akuntansi dan Manajemen, 2016)
This study aimed to examine the effect of tax planning and mechanisms of good corporate governance (GCG) to corporate value and to test the effect of transparency of information on the influence of tax planning and mechanisms of good corporate governance (GCG) with the value of the company. The population in this study manufacturing consumer goods industry sectors listed on the Stock Exchange in 2012-2015. The sampling method using purposivesampling with a final total sample of 68 companies. The analysis technique used is Moderating Regression Analysis (MRA). The analysis showed that the independent variables are tax planning, managerial ownership, institutional ownership, and audit quality have no effect on firm value. While the composition of the independent board positive effect on firm value. Tax planning and mechanisms of good corporate governance (GCG) jointly affect the value of the company, as well as the transparency of information can weaken the influence between tax planning and mechanisms of good corporate governance (GCG) to corporate value.